2011
DOI: 10.1007/s12088-011-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Crossfeeding and Uptake Studies on Hydroxamate Siderophore of Alcaligenes faecalis

Abstract: We report the production of two types of siderophores namely catecholate and hydroxamate in modified succinic acid medium (SM) from Alcaligenes faecalis. Two fractions of siderophores were purified on amberlite XAD, major fraction was hydroxamate type having a λ(max) at 224 nm and minor fraction appeared as catecholate with a λ(max) of 264 nm. The recovery yield obtained from major and minor fractions was 297 and 50 mg ml(-1) respectively. The IEF pattern of XAD-4 purified siderophore suggested the pI value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hydroxamic acids, for example, are widely found as functional groups of bacterial antibiotics ( 64 ) and siderophores ( 65 ). A. faecalis has also been reported to produce hydroxamate-containing siderophores ( 66 ). However, the biosynthesis of siderophores seems unlikely in our experiments, considering that A. faecalis was cultured with an excess of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxamic acids, for example, are widely found as functional groups of bacterial antibiotics ( 64 ) and siderophores ( 65 ). A. faecalis has also been reported to produce hydroxamate-containing siderophores ( 66 ). However, the biosynthesis of siderophores seems unlikely in our experiments, considering that A. faecalis was cultured with an excess of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Production of catecholate and hydroxamate types of siderophore has been reported by Sayyed and Chincholkar (2006) . Sayyed and Chincholkar (2011) and Valdez-Nuñez and Rivera-Jacinto (2022) reported the bioremediation of heavy metal-contaminated soil using siderophore-producing microorganisms. Akhtar et al (2021) reported the potential of B. cereus to improve plant growth under chromium-contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophores are small molecular weight ferric-specific ligands produced by various microorganisms for their iron nutrition ( Sayyed and Chincholkar, 2011 ). Although siderophores are ferric-specific ligands, they can also bind multiple other metal ions in the environment ( Schwyn and Neiland, 1987 ; Payne, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strains lacking fhuE were more sensitive to the chelator suggesting FhuE may be important for uptake of siderophores produced by F. columnare . FhuA, FecA, and the other identified outer membrane receptors may assist with the uptake of F. columnare siderophores or they could be used to take up siderophores produced by other bacteria as is seen in other pathogens ( Magarinos et al., 1994 ; Sayyed et al., 2011 ). FhuA, FecA, and the 12 other predicted TonB-dependent iron receptors ( Table 1 ) may take up iron complexed with other (non-siderophore) molecules.…”
Section: Discussionmentioning
confidence: 99%